2013
DOI: 10.1002/berj.3027
|View full text |Cite
|
Sign up to set email alerts
|

Being ‘nuff’ and ‘scudding class’: exploring girls’ and boys’ perceptions of popularity, gender and achievement in Antiguan secondary schools

Abstract: This paper will report on the findings from classroom observations and focus group discussions conducted on the topic of popularity and fitting in at school with girls and boys from four government secondary schools in Antigua. The findings show that whilst boys did experience difficulties negotiating academic success and acceptable masculinities, the consensus was that popularity was associated with low achievement for both girls and boys. However, there was evidence that some girls were able to work hard and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Angelika refers here to the link between popular 'cliques' and appearance that has been repeatedly found in school studies (see e.g. Francis et al, 2012, Cobbett, 2014 and satirized in fictional contexts such as the 1995 movie Clueless and the 2009-2015 American TV show Glee), to the extent that she can 'shorthand' her discussion with the interviewer by labelling such groups the 'cliché groups'. As we have mentioned above, studies of gender and popularity amongst teens and pre-teens has often found that the perceived 'capital' of having looks or appearance deemed heterosexually attractive is a highly valuable one in terms of moving up status ladders at school, especially for girls.…”
Section: 'It Is Like School Sometimes You Know': Popularity Friendsmentioning
confidence: 99%
“…Angelika refers here to the link between popular 'cliques' and appearance that has been repeatedly found in school studies (see e.g. Francis et al, 2012, Cobbett, 2014 and satirized in fictional contexts such as the 1995 movie Clueless and the 2009-2015 American TV show Glee), to the extent that she can 'shorthand' her discussion with the interviewer by labelling such groups the 'cliché groups'. As we have mentioned above, studies of gender and popularity amongst teens and pre-teens has often found that the perceived 'capital' of having looks or appearance deemed heterosexually attractive is a highly valuable one in terms of moving up status ladders at school, especially for girls.…”
Section: 'It Is Like School Sometimes You Know': Popularity Friendsmentioning
confidence: 99%
“…Hegemonic masculinity in the English-speaking Caribbean is also characteristic of boys intentionally displaying disinterest in schooling (Cobbett, 2014;Plummer et al, 2008); the sanctioning of homophobia, and rejecting feminine-appearing activities (Chevannes, 2001;Parry, 1996;Plummer et al, 2008). Parry concluded that the typology of masculinity that is valued inside this region is oftentimes not conducive to Afro-Caribbean boys aspiring in academics or men entering the teaching profession.…”
Section: The English-speaking Caribbean Boy Underachievementmentioning
confidence: 99%
“…School type or location in this region can often be used as a proxy for the average socioeconomic status of the school (Bailey, 2004), thereby suggesting a possible socioeconomic and sex interaction effect as well. A clear example of this is from Antiguan schools where the lowest performing boys in private schools attain higher than the highest performing girls in government schools (George, 2012 as cited in Cobbett, 2014) which demonstrates that class is more important than sex. Finally, Brown (2005) found that Hindu Indo-Trinidadian boys performed similarly to their female counterparts in math suggesting an ethnic by sex interaction affect here too in countries that have more ethnically diverse populations.…”
Section: School Organizational Factorsmentioning
confidence: 99%
“…There is a rich research tradition that investigates possible adverse circumstances of highperformers in the context of incongruent gender identity (e.g., Bailey, 2004;Cobbett, 2014;Freeman, 2004;Leder, 2004;Martino, 1999;Pérez et al, 1998;Warrington et al, 2000). One consistent finding is that for many boys the preservation of their status among a group of boys requires them to avoid adopting the image of someone who works hard towards academic goals.…”
Section: Introductionmentioning
confidence: 99%
“…2014;Kramer, 1991;Renold & Allan, 2006). In order to minimize the gender related image of a highperformer (Cobbett, 2014;Francis, 2009;Renold, 2001;Renold & Allan, 2006) gifted girls take a keen interest in displaying traditionally feminine categories like their looks or having a boyfriend. And indeed, those girls who maintain this balance had a more positive academic and social reputation with teachers and peer groups.…”
Section: Introductionmentioning
confidence: 99%